The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/head.13134
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Prescription Drug Coverage for Triptans: Analysis of Insurance Formularies

Abstract: There are substantial variations in coverage and quantity limits and a high degree of complexity in triptan coverage for both government and commercial plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The coverage of generic and brand name triptans by both commercial and noncommercial insurers was very heterogeneous, although generic sumatriptan, naratriptan, zolmitriptan, and rizatriptan were covered by nearly all plans. The study demonstrated that equitable access was problematic, particularly for specific triptans and formulations, quantity limits, and requirements for step therapy that may be major barriers to care impacting patients specifically with government (noncommercial) insurance plans . The efficacy and cost effectiveness of treatment for, as well as health care utilization by, individuals with a low socioeconomic/educational status and migraine should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…The coverage of generic and brand name triptans by both commercial and noncommercial insurers was very heterogeneous, although generic sumatriptan, naratriptan, zolmitriptan, and rizatriptan were covered by nearly all plans. The study demonstrated that equitable access was problematic, particularly for specific triptans and formulations, quantity limits, and requirements for step therapy that may be major barriers to care impacting patients specifically with government (noncommercial) insurance plans . The efficacy and cost effectiveness of treatment for, as well as health care utilization by, individuals with a low socioeconomic/educational status and migraine should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, some may cost in excess of $12 per dose and are strictly limited in monthly quantity on many Medicaid plans. 10 Oral NSAIDs and combination analgesics with caffeine are considered reasonable first-line treatment choices for mild to moderate migraine attacks or severe attacks that have previously responded to NSAIDs. Many generic NSAIDs are covered on Medicaid plans.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that patients' migraine medication regimens should be regularly assessed for appropriate medication use and to ensure that their medications are still effective.Another common circumstance for a migraine-related ED visit was not having prescribed abortive medication on hand at the migraine onset; almost one in six total ED visits may have been preventable had patients had their medications available. Prescription insurance payers often set monthly quantity limits for triptans due to risk for medication overuse headache, and may impact lack of triptan availability 25. However, if patients run out of triptans due to frequent use, new or additional migraine preventive therapy or a dose adjustment of their current therapy would be warranted 8.…”
mentioning
confidence: 99%